Model of care and chance of spontaneous vaginal birth: a prospective, multicenter matched-pair analysis from North Rhine-Westphalia - Sophia L. Tietjen; Marie-Therese Schmitz; Andrea Heep; Andreas Kocks; Lydia Gerzen; Matthias Schmid; Ulrich Gembruch; Waltraut M. Merz (BMC, 2021)
Abstract Background Advantages of midwife-led models of care have been reported; these include a higher vaginal birth rate and less interventions. In Germany, 98.4% of women are giving birth in obstetrician-led units. We compared the outcome of birth planned in alongside midwifery units (AMU) with a matched group of low-risk women who gave birth in obstetrician-led units. Methods A prospective, controlled, multicenter study was conducted. Six of seven AMUs in North Rhine-Westphalia participated. Healthy women with a singleton term cephalic pregnancy booking for birth in AMU were eligible. For each woman in the study group a control was chosen who would have been eligible for birth in AMU but was booking for obstetrician-led care; matching for parity was performed. Mode of birth was chosen as primary outcome parameter. Secondary endpoints included a composite outcome of adverse outcome in the third stage and / or postpartum hemorrhage; higher-order obstetric lacerations; and for the neonate, a composite outcome (5-min Apgar < 7 and / or umbilical cord arterial pH < 7.10 and / or transfer to specialist neonatal care). Statistical analysis was by intention to treat. A non-inferiority analysis was performed. Results Five hundred eighty-nine case-control pairs were recruited, final analysis was performed with 391 case-control pairs. Nulliparous women constituted 56.0% of cases. For the primary endpoint vaginal birth superiority was established for the study group (5.66%, 95%-CI 0.42% - 10.88%). For the composite newborn outcome (1.28%, 95%-CI -1.86% - -4.47%) and for higher-order obstetric lacerations (2.33%, 95%-CI -0.45% - 5.37%) non-inferiority was established. Non-inferiority was not present for the composite maternal outcome (-1.56%, 95%-CI -6.69% - 3.57%). The epidural anesthesia rate was lower (22.9% vs. 41.1%), and the length of hospital stay was shorter in the study group (p < 0.001 for both). Transfer to obstetrician-led care occurred in 51.2% of cases, with a strong association to parity (p < 0.001). Request for regional anesthesia was the most common cause for transfer (47.1%). Conclusion Our comparison between care in AMU and obstetrician-led care with respect to mode of birth and other outcomes confirmed the superiority of this model of care for low-risk women. This pertains to AMU where admission and transfer criteria are in place and adhered to.